2005
DOI: 10.1002/jcb.20611
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral effect of Phyllanthus nanus ethanolic extract against hepatitis B virus (HBV) by expression microarray analysis

Abstract: Ethanolic extract of Phyllanthus nanus (P. nanus) treatment exhibited potent antiviral activity against Hepatitis B virus (HBV). The effects of these extracts on HBV in the HBV genome integrated cell lines--Alexander cells and HepG2 2.2.15 cells were examined. Experimental results showed that the ethanolic extract of P. nanus produced suppressive effect on HBsAg secretion and HBsAg mRNA expression. The extract also inhibited HBV replication as measured by HBV DNA level in vitro. In addition, using a duck HBV (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…TNF-α has been found to be a very important pathogenic mediator in patients with alcoholic liver disease and viral hepatitis, as well as in many animal liver injury models [27] . Recent research showed that the activation of the annexin A7 (Axn7) gene and the expression of the Axn7-GFP fusion protein could cause a decrease in HBsAg secretion [28] . However, the precise mechanism of the anti-HBV activity of hyperoside needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α has been found to be a very important pathogenic mediator in patients with alcoholic liver disease and viral hepatitis, as well as in many animal liver injury models [27] . Recent research showed that the activation of the annexin A7 (Axn7) gene and the expression of the Axn7-GFP fusion protein could cause a decrease in HBsAg secretion [28] . However, the precise mechanism of the anti-HBV activity of hyperoside needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We have isolated and identified several chemical extracts and pure compounds from Chinese medicine with anti-hepatoma, anti-multidrug resistant hepatoma and antihepatitis viral effects. [16][17][18][19] Essential oil of Ezhu and it active ingredients have been widely used for treatment of malignant tumors in China. 4,5 Furanodiene, an ingredient from Ezhu oil, has been identified to have protective effects against D-galactosamine/ lipopolysaccharide/TNFa induced liver injury.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of bioactive components in Angelica sinensis is very important not only for the quality control of crude botanical drugs but also for elucidating the therapeutic principle. With the aim of dissecting the molecular pharmacological actions of active ingredients originating from botanical materials, novel approaches have been adopted [Lam et al, 2006]. Moreover, we have used a new approach combining biomembrane extraction and high performance liquid chromatography to identify ferulic acid (FA), ligustilide, senkyunolide H, and senkyunolide I, which are some potentially bioavailable components in Angelica sinensis [Dong et al, 2005].…”
mentioning
confidence: 99%